2013
DOI: 10.1155/2013/541804
|View full text |Cite
|
Sign up to set email alerts
|

Rossomyrmex, the Slave-Maker Ants from the Arid Steppe Environments

Abstract: The host-parasite genera Proformica-Rossomyrmex present four pairs of species with a very wide range of distribution from China to Southeastern Spain, from huge extended plains to the top of high mountains. Here we review (1) the published data on these pairs in comparison to other slave-makers; (2) the different dispersal ability in hosts and parasites inferred from genetics (chance of migration conditions the evolutionary potential of the species); (3) the evolutionary potential of host and parasite determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
5

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 38 publications
0
8
0
5
Order By: Relevance
“…They have been suggested to represent an intermediate parasitic stage, between those species without predominant brood raiding, and obligate slave‐making species (Topoff and Zimmerli [], Ruano et al. []). 2.When the death rate d of the parasite is independent of its trait value, Corollary implies that the trait component of the host‐only equilibrium Ex10u1u2 can be an ESS when the parasite is obligate; and the trait component of the facultative parasite‐only equilibrium E0x2u1u2 can also be an ESS. …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They have been suggested to represent an intermediate parasitic stage, between those species without predominant brood raiding, and obligate slave‐making species (Topoff and Zimmerli [], Ruano et al. []). 2.When the death rate d of the parasite is independent of its trait value, Corollary implies that the trait component of the host‐only equilibrium Ex10u1u2 can be an ESS when the parasite is obligate; and the trait component of the facultative parasite‐only equilibrium E0x2u1u2 can also be an ESS. …”
Section: Resultsmentioning
confidence: 99%
“…These species display the ability to vary behaviorally between reliance on parasitism of other ants, and producing their own worker offspring. They have been suggested to represent an intermediate parasitic stage, between those species without predominant brood raiding, and obligate slave-making species (Topoff and Zimmerli [1991], Ruano et al [2013] -7); (ii) the variances of the proposed trait functions, i.e., σ K 1 , σ K 2 , and σ d , play essential roles in guaranteeing the trait component (0, 0) of the local stable coexistence equilibrium (x * 1 , x * 2 , 0, 0) being an ESS; (iii) when the parasite death rate d is large, the host can have ESS that drive the parasite extinct globally; and (iv) Large variances of the parasite carrying capacity σ K 2 and of the parasitism efficiency σ a are required to make sure of the trait component (0, 0) of (x * 1 , x * 2 , 0, 0) being an ESS. In addition, we have following interesting results: (a) It is possible to have locally stable coexistence equilibrium (x * 1 , x * 2 , u * 1 , u * 2 ) with u * 1 , u * 2 > 0 (see Proposition (4.1)) but the trait components of these equilibria may not be ESS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mycocepurus castrator inquiline parasites experimentally placed near a host nest quickly entered the nest signifying that they are able to sense their host (Rabeling and Bacci, 2010). Dulotic slave-making species and Megalomyrmex agro-predator raiders also find host colonies as young queens or later as scout workers (Boudinot et al, 2013;Ruano et al, 2013). This suggests they are using host-derived chemical cues to find the host nest and brood ( Table 1).…”
Section: Trail Following Social Parasites (Hymenoptera: Formicidae)mentioning
confidence: 99%
“…The first one is the most studied, with 14 known species (Trager, ) parasitizing ants of the genus Formica and with several phylogenetic studies supporting Emery's rule in its loose version (e.g., Chen, Zhou, Ye, & Lu, ; Hasegawa, Tinaut, & Ruano, ; Muñoz‐López et al., ; Ward et al., ). In contrast, Rossomyrmex consists of only four species, which parasitize species of the ant genus Proformica (Ruano, Sanllorente, Lenoir, & Tinaut, ): P. epinotalis Kuznetsov‐Ugamsky, 1927 parasitized by R. proformicarum Arnoldi, 1928 in the North shore of the Caspian Sea (Russia); P. cf epinotalis and R. quandratinodum Xia and Zheng, 1995 are found between China and Kazakhstan; P. korbi Emery, 1909 and R. anatolicus Tinaut, in the plains of Anatolia (Turkey); and P. longiseta Collingwood, 1978, with a patchy distribution in high mountains of southeastern Spain parasitized in three of them by R. minuchae Tinaut, . In addition, it has been recently found that P. nasuta Nylander, 1856 can be parasitized by R. minuchae (Azcárate et al., ).…”
Section: Introductionmentioning
confidence: 99%